Total inferior border ostectomy versus T-shape genioplasty for chin narrowing combined with mandibular contouring. Issue 12 (December 2022) - Wang, Y.; He, Y.; Al-Watary, M.Q.H.; Bi, D.; Song, L.; Li, J.
Abstract: The objective of this study was to compare the indications and outcomes of the total inferior border ostectomy and T-shape genioplasty. A retrospective study was conducted using the clinical notes and records of patients who underwent total inferior border ostectomy (group 1, n = 42) and T-shape genioplasty (group 2, n = 60). The outcomes were evaluated by assessment of computed tomography images combined with medical records and photographs. Lower facial height, chin width, chin symmetry, and facial proportions, as well as patient satisfaction and complications were investigated. The data were collected preoperatively and 6–24 months postoperatively. All 102 patients showed an improved lower facial contour. No severe complications were observed during the follow-up period. Although the postoperative lower to midfacial height ratios were similar in the two groups ( P = 0.080), both the preoperative and postoperative chin width to lower facial height ratios were lower in group 1 (both P < 0.001). A larger amount of chin narrowing, as well as better chin symmetry were observed in group 1 ( P < 0.001). In conclusion, compared to the T-shape genioplasty, the total inferior border ostectomy is well suited for a longer, wider, and more asymmetrical chin. The surgical options should be considered and chosen quantitatively to achieve aesthetically pleasing results.